2016
DOI: 10.1021/acs.est.6b02797
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation Kinetics of 1,4-Dioxane in Chlorinated Solvent Mixtures

Abstract: This study investigated the impacts of individual chlorinated solvents and their mixtures on aerobic 1,4-dioxane biodegradation by Pseudonocardia dioxanivorans CB1190. The established association of these co-occurring compounds suggests important considerations for their respective biodegradation processes. Our kinetics and mechanistic studies demonstrated that individual solvents inhibited biodegradation of 1,4-dioxane in the following order: 1,1-dichloroethene (1,1-DCE) > cis-1,2-diochloroethene (cDCE) > tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 59 publications
9
52
0
Order By: Relevance
“…Examples of techniques that have successfully removed 1,4-dioxane from contaminated groundwater include biodegradation (Zhang et al, 2016; Steffan, 2007) and chemical oxidation (Schreier et al, 2006; Vescovi et al, 2010). Advanced oxidative processes (AOPs) have been implemented at multiple sites to treat extracted groundwater containing 1,4-dioxane.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of techniques that have successfully removed 1,4-dioxane from contaminated groundwater include biodegradation (Zhang et al, 2016; Steffan, 2007) and chemical oxidation (Schreier et al, 2006; Vescovi et al, 2010). Advanced oxidative processes (AOPs) have been implemented at multiple sites to treat extracted groundwater containing 1,4-dioxane.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum power densities obtained in this study were comparable to the reported values in the literature for treatment of phenanthrene and benzene, as well as benzene‐ and ammonium‐contaminated groundwater in MFCs, that is, ~25–300 mW/m 3 (Adelaja et al, ; Wei et al, ). Groundwater is often contaminated by a variety of organic and inorganic contaminants, for example, 1,4‐dioxane is often found co‐contaminated with chlorinated hydrocarbons (e.g., TCE and TCA; Stefan & Bolton, ; Zhang, Gedalanga, & Mahendra, ). Degradation of chlorinated hydrocarbons has been widely studied on cathodes of bioelectrochemical systems; however, the process generally needs supplying external voltage (Aulenta et al, ; LeitĂŁo et al, ; Pous, Balaguer, Colprim, & Puig, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that the co-presence of VOCs, such as trichloroethene (TCE) and 1,1-dichloroethene, diminished 1,4-dioxane degradation by several 1,4-dioxanedegrading bacteria by (1) competition between 1,4-dioxane and VOCs on monooxygenases that catalyze the initial oxidation of 1,4-dioxane and also the oxidation of VOCs, (2) repression of degradation gene expression, and (3) toxic effects of themselves or their degradation products [35,36]. It has also been reported that some metals have inhibitory effects on 1,4-dioxane degradation by P. dioxanivorans CB1190 [37].…”
Section: On-site Treatment Of 14-dioxane-contaminated Groundwater Usmentioning
confidence: 99%